A formalization of one of the main claims of “Mutations in NGLY1 cause an inherited disorder of the endoplasmic reticulum–associated degradation pathway” by Enns et al. 2014 - Queralt-Rosinach, Núria (Data Science, 2022)
Enns et al. claimed in previous work that NGLY1 deficiency is a novel autosomal recessive disorder of the ERAD pathway. We present here a formalization of that claim, stating that all things of class “NGLY1 deficiency” that are in the context of a thing of class “human” always have a relation of type “is caused by” to a thing of class “dysfunction of ERAD pathway” in the same context.